2014
DOI: 10.1371/journal.pone.0112066
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Vagus Nerve Stimulation on Depressive-Like Behavior, Hyperglycemia and Insulin Receptor Expression in Zucker Fatty Rats

Abstract: Depression and type 2 diabetes (T2D) are common comorbid diseases and highly prevalent in the clinical setting with an unclarified mechanism. Zucker diabetic fatty (ZDF, fa/fa) rats natively develop T2D with hyperglycemia and hyperinsulinemia. Here we studied whether ZDF rats also innately develop depression, what a correlation is between depression and T2D, whether insulin receptor (IR) expression is involved in, and whether transcutaneous auricular vagus nerve stimulation (taVNS) would be beneficial in ameli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 34 publications
2
33
0
Order By: Relevance
“…When compared to control heterozygotes or wild-types, only ZDF rats homozygous for the fatty (fa/fa) leptin receptor mutation develop cardinal symptoms of glucose-intolerant diabetes 13 including hyperphagia 69,83 , hyperinsulinemia 51, 65, 92 , obesity 69 , hyperglycemia 69, 73, 101 , elevated HbA1c 51, 92 , and increased MG-AGE 89 . In the first experiment we characterized the progression of hyperglycemia and pain-like behavior in diabetic ZDF and control ZL rats.…”
Section: Resultsmentioning
confidence: 99%
“…When compared to control heterozygotes or wild-types, only ZDF rats homozygous for the fatty (fa/fa) leptin receptor mutation develop cardinal symptoms of glucose-intolerant diabetes 13 including hyperphagia 69,83 , hyperinsulinemia 51, 65, 92 , obesity 69 , hyperglycemia 69, 73, 101 , elevated HbA1c 51, 92 , and increased MG-AGE 89 . In the first experiment we characterized the progression of hyperglycemia and pain-like behavior in diabetic ZDF and control ZL rats.…”
Section: Resultsmentioning
confidence: 99%
“…However, in the majority of the patients treated with VNS, stimulation occurs at the site of the cervical vagus nerve and both, efferent and afferent nerve fibers are activated. Thus, despite the reports from animal studies suggesting beneficial metabolic effects of VNS at more peripheral sites than the cervical vagus nerve (Li et al 2014;Malbert et al 2017) or with selective efferent cervical VNS (Peitl et al 2005;Meyers et al 2016), the question if nonselective (combined efferent and afferent) VNS at the site of the cervical vagus nerve may deteriorate glucose tolerance and place patients at risk for type 2 diabetes is highly relevant and important because our previous study demonstrated inhibition of insulin release despite marked increases in blood glucose levels during non-selective (intact nerve) and selective afferent (dissected nerve) cervical VNS. To further explore this question, we hypothesized that chronic cervical VNS of the intact vagus nerve inhibits glucose-induced insulin release and, thus, impairs glucose tolerance in conscious rats.…”
Section: Introductionmentioning
confidence: 89%
“…Indeed, studies in animals suggest that chronic stimulation of vagal nerve branches other than the cervical vagus nerve may have beneficial effects on glucose metabolism. For example, chronic bilateral stimulation of the subdiaphragmatic vagal nerves improved insulin sensitivity in diet-induced obesity in mini-pigs (Malbert et al 2017) and transcutaneous auricular vagus nerve stimulation prevented the increase in blood glucose levels and glycosylated HbA1c in Zucker diabetic fatty rats (Li et al 2014). Thus, it is possible that stimulation of more peripheral branches of the vagus nerve (e.g., subdiaphragmatic) improves glucose metabolism through efferent signaling to metabolic end-organs, such as the pancreas or the liver.…”
Section: Introductionmentioning
confidence: 99%
“…Other potential clinical indications for VNS, such as heart failure (Premchand et al, 2014;Zannad et al, 2015;Gold et al, 2016), Crohn's disease (Bonaz et al, 2016), chronic pain management (Chakravarthy et al, 2015), and obesity (Bodenlos et al, 2007;Pardo et al, 2007;Bodenlos et al, 2014) are emerging. There have also been promising reports in rats (Li et al, 2014) and humans (Huang et al, 2014;Huang et al, 2016), suggesting a potential beneficial role of noninvasive transcutaneous auricular VNS in diabetes. In contrast to these studies utilizing noninvasive transcutaneous auricular VNS, studies on the effects of invasive cervical VNS on glucose homeostasis are less promising.…”
Section: Introductionmentioning
confidence: 99%